Analisis Fiqh Muamalah terhadap Praktik Pinjaman Kelompok di Platform Fintech Amartha dalam Perspektif Hukum Ekonomi Syariah - Gantina, Anna Delfianty; Haikal, M. Awalul; J, Jaenudin; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the legal position and compliance of Amartha’s peer-to-peer lending scheme within the framework of Sharia principles, focusing on the legitimacy of the wakalah bil ujrah contract and its alignment with Indonesian positive law. Using a normative juridical method, this research relies on primary legal materials including OJK regulations governing fintech lending and relevant DSN-MUI fatwas, supported by secondary materials such as journals, sustainability reports, and academic analyses. The findings indicate that Amartha’s business model featuring group-based financing, fixed service fees, and risk-sharing mechanisms generally aligns with the governance requirements stipulated in POJK and the contractual parameters defined in fatwas on wakalah, ujrah, and P2P financing ethics. This study concludes that while Amartha’s model is legally structured to comply with Sharia and positive law, stronger regulatory enforcement and standardized disclosures are necessary to ensure optimal consumer protection and Sharia-compliant financial practices.